Implementasi Program Bimbingan dan Konseling dalam Menangani Permasalahan Sosial pada Siswa - Patrisia, Shelin; Dhorim, Muhammad; Monica, Shellanda; Putri, Tivany Elka (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
This study intends to analyse the implementation of the guidance and counselling program in addressing the social challenges faced by students at SD Negeri 41 Pagaralam. Social issues, such as bullying, difficulties in peer relationships, and social anxiety, can greatly affect students' social and emotional development. The research used a descriptive qualitative approach, utilising data collection techniques like observation, in-depth interviews, and documentation. The participants were the school principal, guidance and counselling staff, and students who had received counselling services. The collected material was analysed using theme analysis. The results indicate that the guidance and counseling program is successful in assisting students in overcoming their social challenges. The program offers students an opportunity to express their concerns, develop social skills, and receive necessary emotional support. Furthermore, the active involvement of the school principal, support from parents, and collaboration with relevant stakeholders were essential factors contributing to the program's success. In conclusion, a well-implemented guidance and counseling program can enhance students' social interactions and foster their emotional well-being.